Specimen design for extreme uniaxial tension‐compression tests of rubber materials. Issue 1 (18th November 2019) - Kanzenbach, Lars; Schlomka, Clemens; Gelke, Sören; Ihlemann, Jörn
Abstract: In this contribution a new measurement strategy is presented, which enables in combination with an optimized specimen‐setup the investigation of strains up to a compression level of −70%. The specimen‐setup itself consists of a slender dumbbell structure and a mounting geometry. The main idea of the new measurement strategy is, that for almost incompressible materials the average strain in the symmetry plane can be derived from the tangential strain at the surface. For this, the new measurement strategy is derived, simulated and experimentally tested. Finally, phenomenological characteristics of rubber, like Payne effect, Mullins effect, permanent set, relaxation and creep can be investigated at such extreme compression levels.